Clinical Manifestations of Alport Syndrome-Diffuse Leiomyomatosis Patients With Contiguous Gene Deletions in COL4A6 and COL4A5 - Zhou, Xi; Wang, Jingjing; Mao, Jianhua; Ye, Qing (Frontiers in Medicine, 2021)
Alport syndrome-diffuse leiomyomatosis (ATS-DL) is a rare type of X-linked Alport syndrome (ATS) resulting from contiguous deletions of 5' exons of COL4A5 and COL4A6. Studies have suggested that diffuse leiomyomatosis is associated with the characteristic localization of the COL4A6 gene deletion breakpoint. An electronic database was searched for all studies accessing ATS-DL to analyze the clinical characteristics, gene deletion breakpoints of patients with ATS-DL, and ATS-DL's mechanism. It was found that the proportion of de novo mutations of ATS-DL was significantly higher in female probands than male probands (78% Vs. 44%). The clinical manifestations of AST-DL in female probands were few and mild. The incidence of proteinuria and ocular abnormalities was much lower in female probands than in male probands, and there was generally no sensorineural hearing loss or chronic kidney disease (CKD) progression to stage 3 in female probands. The contiguous deletion of the 5’ exons of COL4A5 and COL4A6, with the breakpoint located in the intron 3 of COL4A6, was the critical genetic defect causing ATS-DL. However, the mechanism of characteristic deletion of COL4A6 contributes to diffuse leiomyomatosis is still unknown. In addition, characteristic contiguous deletion of COL4A5 and COL4A6 genes in ATS-DL may be related to transposed elements.